Development of the train traffic regulation method for “Rail Baltica” line based on the implementation of the European train traffic control systems - Valentinovič, Larisa; Sivilevičius, Henrikas (International Conference “Environmental Engineering”, 2017)
This article focuses on analyzing the systems and methods used for the interval regulation of train movement on “Rail Baltica” line in “Lithuanian Railways”. The method discussed in the article can be viewed as a combination of several management automation solutions and it is based on the implementation of the European Railway Traffic Management System (ERTMS). As it is known, the ERTMS provides an interoperable European railway network. The primary objective is to improve the quality of train traffic and to make railway transport safer and more comfortable. In order to ensure new traffic prevision for Lithuanian Railways, new interval regulation methods and traction calculations must be used. This developed method is more useful than the previous methods as it allows to shape an efficiently automated and optimized scheduling process as well as to improve line capacity and efficiency. This paper proposes the development of a moving block train control system. The calculations were made using the intervals between trains. The interval and block-section borders are not fixed by traffic signs or traffic-lights. Instead, they move after the train in the front, creating a flexible interval regulation system. The results showed that the implementation of the method had a positive impact on the operators’ performance and allowed to reduce energy consumption and to increase the speeds of train movement. The paper also presents a statistical figure portraying railway accidents and railway operation accident reports before and after the implementation of the ERTMS. The results of the analysis showed that the simple mentation of the European Train Traffic control systems and the interval regulation of train movement method will provide high throughput and carrying capacity, traffic safety and also increase the productivity of operation procedures.